Math, asked by rinasingh20134, 1 year ago

5. Find x in each of the following:
() 7* 4+ (x * 3) = 7 (4+6)
(i) (
( 9 * 8) + ( 8 * 8) -- ( 9 + 8 ) * x​

Answers

Answered by veeraboyina3463
1

7*4+(x*3)=7(4+6)

28+(x*3)=70

(x*3)=70-28

(x*3)=42

x=14

hence proved

Answered by abhishek6829
3

Answer:

(1) answer = x = 14

(2) answer =

Step-by-step explanation:

(I) solution =

7 \times 4 + (x \times 3 = 7(4 + 6)

28 + x \times 3 = 28  + 42

x  = 28  -   28 + 42 \div 3

x = 0 + 42 \div 3

x = 42 \div 3

x = 14

(ii) solution =

(9 \times 8) +(8 \times 8) - (9  +  8) \times x = 0

,

72 + 64 - 17  \times x = 0

136 - 17 \times x = 0

119 \times x = 0

119 = 0 \div x

119 = 0

Similar questions